The Role of Cloud Storage in Rebuilding Governmental Data After Conflict: A Case Study of Sudan 2023 - Sabah Abdellatif Hassan Ahmed (International Journal of Computers and Informatics, 2024)
The aim of this research is to assess the Role of Cloud Storage in Rebuilding Governmental Data After Conflict, with a deeper insight into Sudanese case. To investigate the role of cloud storage in rebuilding governmental data after conflict in Sudan, this study employs a quantitative research methodology. The primary data collection instrument is a structured questionnaire designed to gather insights and perspectives from 80 participants of key stakeholders involved in the cloud storage adoption and data reconstruction efforts in Sudan, including (IT professionals and data management experts, Senior-level government officials and policymakers, Representatives from cloud service providers, End-users and data consumers from various government agencies). The collected data underwent accurate statistical analysis, including descriptive and inferential techniques, to identify patterns, trends, and relationships among the variables under investigation. Quantitative data was analyzed using "SPSS" statistical software. The findings of the research revealed that, a total of 18 participants representing (22.5%) agree that there is a high level of awareness and understanding of cloud storage technologies among government agencies in Sudan, while 28 participants representing (35%) disagree. Which indicates the need of spreading the awareness and understanding of cloud storage technologies among government agencies in Sudan. Furthermore, Pearson Chi-Square test was used to measure the role of cloud storage in rebuilding governmental data after conflict in Sudan, a significance value of (0.021) which is less than (p-value=.05) suggests that there is a significant role of cloud storage in rebuilding governmental data after conflict in Sudan.